Fostering deep renovation and unburdening homeowners through digital platforms. Issue 1 (1st September 2022) - Greco, Angela; Olivadese, Rosamaria
Abstract: The customer journey of private homeowners towards deep renovation poses several challenges resulting in users not implementing energy efficiency measures. The conversion rate from orientation to implementation needs to increase and the whole renovation process to accelerate. Platforms are seen as playing a key role in accelerating renovations, acting as intermediary between the customer and the providers, reducing the friction between demand and supply. In this paper, we provide an overview of roles and impacts of digital platforms accelerating sustainability in the Dutch built environment. We analysed the outlook of 64 existing (digital) platforms to study their role in the customers journey. Our findings suggest that platforms offering individual guidance in the orientation phase of the customer journey are more likely to witness homeowners choosing for one or multiple energy efficient interventions as opposed to collective initiatives.